2001
DOI: 10.1002/ddr.1209
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of the anxiogenic effects of ethanol withdrawal

Abstract: Although anxiety is a major feature of ethanol withdrawal (EW) and much of treatment related to EW is focused on amelioration of the anxiety experienced during EW, less attention has been given to the anxiogenic effects of EW than to the convulsant effects. In this article, we review the animal literature on the anxiogenic effects of EW. Both GABA A and serotonin (5-HT) receptors are important targets in the treatment of anxiety. The roles of each of these two receptors on the anxiogenic effects of EW as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 172 publications
3
17
0
Order By: Relevance
“…On the other hand, alcoholism and alcohol abuse often involve heavy bouts of binge-like drinking interspersed with periods of abstinence, while some signs of withdrawal (such as fatigue, tremor, anxiety and depression) may be observed even after acute ingestion of substantial amounts of alcoholFa phenomenon commonly referred to as acute ethanol withdrawal or hangover (Smith and Barnes, 1983;Bogin et al, 1986;Wiese et al, 2000). Although many studies have consistently demonstrated increases in anxiety-like behavior during the withdrawal period after chronic exposure to ethanol in rodents (File et al, 1991(File et al, , 1993Lal et al, 1991;Knapp et al, 1993;Gatch et al, 1999;Gatch and Lal, 2001), there are limited experimental findings regarding this symptom after a single ethanol challenge dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, alcoholism and alcohol abuse often involve heavy bouts of binge-like drinking interspersed with periods of abstinence, while some signs of withdrawal (such as fatigue, tremor, anxiety and depression) may be observed even after acute ingestion of substantial amounts of alcoholFa phenomenon commonly referred to as acute ethanol withdrawal or hangover (Smith and Barnes, 1983;Bogin et al, 1986;Wiese et al, 2000). Although many studies have consistently demonstrated increases in anxiety-like behavior during the withdrawal period after chronic exposure to ethanol in rodents (File et al, 1991(File et al, , 1993Lal et al, 1991;Knapp et al, 1993;Gatch et al, 1999;Gatch and Lal, 2001), there are limited experimental findings regarding this symptom after a single ethanol challenge dose.…”
Section: Discussionmentioning
confidence: 99%
“…Models of ethanol withdrawal in adult rodents have consistently demonstrated increases in anxiety-like behavior during the withdrawal period after chronic exposure to ethanol (File et al, 1991(File et al, , 1993Lal et al, 1991;Knapp et al, 1993;Gatch et al, 1999;Gatch and Lal, 2001). In contrast, few studies have examined the presence of withdrawal symptoms following a single dose of ethanol in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have consistently demonstrated increases in anxiety-like behavior during the withdrawal period after chronic exposure to ethanol in rodents (Lal et al, 1991;Knapp et al, 1993;Gatch & Lal, 2001), there are limited experimental findings regarding this symptom after a single ethanol challenge dose. Prediger et al (2006) designed an experimental study of acute ethanol withdrawal (hangover) in mice, in which a timedependent development of anxiety-like behavior after an intraperitoneal administration of a single dose of ethanol (4 g/kg) in mice was assessed, and the potential of adenosine A 1 and A 2A receptor agonists in reducing this behavior was evaluated.…”
Section: Adenosine Agonists and Antagonists In The Responses Induced mentioning
confidence: 99%
“…It makes sense, then, that the majority of animal models of EtOH withdrawal are focused on anxiety-like behavior, with consistent effects observed in rodent models such as the elevated plus-maze, light/dark box, social interaction test, and a drug discrimination assay using pentylenetetrazole (Gatch & Lal, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…In more serious conditions, patients presenting this EtOH withdrawal syndrome can present perceptive changes, agitation, mental confusion, significant increases in autonomic arousal, and seizures (Gatch & Lal, 2001;Krystal & Tabakoff, 2002). The most serious condition involves delirium tremens and death by hyperthermia, cardiac arrhythmia, and complications from withdrawal-induced seizures (Longo & Schuckit, 2014).…”
Section: Introductionmentioning
confidence: 99%